Marketing Communication Strategy for Youth Creations Breakfast Market (PASAR KAMU) in Increasing Visitor Enthusiasm - Mufida, Dwi Nanda; Batubara, Abdul Karim (International Journal of Economics (IJEC), 2024)
This research aims to reveal the facts of the phenomenon to the marketing communication strategy carried out by Pasar Kamu in increasing visitor interest. This type of research is field research with a qualitative approach. Data collection techniques are carried out by interviews, observation, and documentation. Data analysis uses the Miles, Huberman, and Saldana model, namely by collecting data, condensing data, presenting data, and drawing conclusions. The results of this study indicate that Pasar Kamu carries out a marketing communication strategy using several components of the marketing communication mix in increasing visitor interest, namely advertising activities, sales promotion activities, interactive marketing activities, and public relations activities. The implementation of marketing communication strategies increases visitors to Pasar Kamu, which is around 1,000 to 2,500 visitors per week and has attracted visitors from within and outside the country.